Epigenetic Regulation of Mesenchymal Stem Cell Differentiation and the role of external response - Zhang Enwei; Xie Jingwen (BIO Web of Conferences)
Mesenchymal stem cells (MSCs) possess important physiological characteristics such as self- proliferation and multipotent differentiation potential, making them highly promising for applications in tissue repair and regeneration. However, the precise mechanisms underlying these properties remain obscure. Epigenetics is a key clue, which works through DNA methylation, histone modifications, and RNA methylation, regulating MSC gene expression without altering the DNA sequence. These modifications have a significant impact on the fate and function of MSC differentiation, determining their multipotent capabilities. This review explores the role and regulatory mechanisms of epigenetics in MSC differentiation, its direct impact on clinical applications such as advancements in regenerative medicine, and how external factors such as mechanical forces, materials, and other environmental conditions influence MSCs through epigenetic modifications.